A PROVISIONAL ACCOUNT OF THE ORCHIDS OF THE ULU BALEH NATIONAL PARK, KAPIT, SARAWAK - Meekiong, Kalu; Tonga, Noweg; Sayok, Alexender Kiew; Sekudan, Tedong; Akmal, Raffi (Forest Department Sarawak, Sarawak, 2020)
The diversity of orchids was surveyed at several localities in the Baleh National Park, in Southeast Sarawak adjacent to the international border between Malaysia and Indonesia (Kalimantan). A total of 75 species, representing 36 genera, was collected. Most of the species were epiphytic. Terrestrial species included Bromheadia finlaysoniana, Corymborkis veratrifolia, Plocoglottis acuminata and the saprophytic Lecanorchis malaccensis. Arundina graminifolia and Dendrobium hosei were very common.